k-4/2=-6

Simple and best practice solution for k-4/2=-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for k-4/2=-6 equation:



k-4/2=-6
We move all terms to the left:
k-4/2-(-6)=0
We add all the numbers together, and all the variables
k+4=0
We move all terms containing k to the left, all other terms to the right
k=-4

See similar equations:

| -3(-3x+5)-2(3-3x)=(-12+16x) | | x^2-100x+81=0 | | g/4−3=1 | | 3+-2u=-1 | | 1=2h−1 | | -5=1−3c | | X(.0825)+x=41 | | 10=5−c | | 10=5−-c | | k/2+4=5 | | k/2+ 4= 5 | | 2f+1=11 | | -5(3-4x)=-175 | | -7(6x-4)=-266 | | 1+2j=3 | | 6(-5-7m)=306 | | 48/60=12/x | | 2/5(x)-3/5=1/3(x)+13/5 | | 6=2.7^4t | | 132=-3(7x-2) | | 32a^2=-8 | | -3x/4+1=-11 | | (4x+27)/2=(x+1)/3 | | 17,950=100+50w | | (x-2)/(-4)+2=5 | | 16/10000=n/3500 | | 1/10000=n/3500 | | 2(x+4)-1=5(x+2) | | 2(x+4)-1=2(x+11) | | 1/1000=x/3500 | | 3(x-1)+4=2(x+11) | | 29-3x=-9x |

Equations solver categories